Relationship of Interalar and Intercommissural Distance with the Width of Maxillary Anterior Teeth - Ghimire, B.; Dhital, S.; Neupane, P. (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: The anterior teeth are primarily selected to satisfy esthetics. Their selection requires the dentist’s artistic skill and scientific knowledge. This clinical study was conducted to explore the relationship of interalar and intercommissural distance with the combined width of maxillary anterior teeth. Materials and Methods: Measurements of the parameters was made using a Digital caliper. The patient was seated up right position and asked to look straight; the intercommisural and interalar width were measured between commissures and ala without applying pressure. The combined width of maxillary anteriors form the distal surface of left and right canines were measured with a dental floss, which was then sectioned and measured. Each parameter was measured three times and the average value was computed and recorded. Results: Mean Interalar, intercommisural and intercanine distance were 34.72 mm, 48.9 mm and 49.61 mm respectively. Statistical analysis revealed a highly significant difference between the interalar width, intercommisural width and intercanine width of male and female respectively. Spearman’s rho analysis showed a highly significant correlation between Inter canine and both inter alar width (r=0.098, p <0.04) and Intercommisural width (r=0.234, p <0.05). Similarly, Spearman’s rho analysis in both sexes showed a highly significant correlation between intercanine and intercommisural width however such correlation was not seen between intercanine and inter alar width. Conclusions: This study concluded that there is significant correlation between interalar and intercommissural width with the combined width of maxillary anterior teeth. The inter alar and inter commissural width may be a useful guideline for the selection and replacement of maxillary anterior artificial teeth.